A Fuzzy System Model for Task Implementation in Extreme Programming Process - (:unkn) unknown (SPRINGER-VERLAG BERLIN, 2011)
Software simulation enables us to see how a software process is working and gives indications of some of the parameters of the process. In this study the implementation of the tasks in extreme programming software process was modeled using a fuzzy system. The inputs of the system are defined as communication between pair programmers, the writing of unit tests and the coding rules, while the output is the implemented task. The defuzzified output of this fuzzy system provides quantitative results that can be used to determine to how good a task has been implemented.
Keywords: software process models; agile software development; extreme programming; fuzzy systems; SIMULATION; LOGIC